The Impact of Audit Committee Composition and Performance on Financial Reporting Quality in Kurdistan’s Industrial Companies - Sardar Jalal Braim; Rebin Bilal Mohammed (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Given the high prevalence of corporate fraud and misconduct worldwide, the demand for financial reporting quality has also been on a high rise. Among the suggested courses of action is audit committee composition and performance. Consequently, the study examines the impact of audit committee composition and performance on financial reporting quality using 277 responses collected from 140 internal audit managers, 120 audit committee members and 17 financial managers of five strategic industries in Erbil, Kurdistan. The responses were regressed using two single regression analysis models with the aid of SPSS version 24. The findings of the study indicated that improvements in both audit committee composition and performance have significant positive effects on financial reporting quality. The study’s theoretical underpinnings are engraved in suggesting that the principal-agent theory’s propositions can be improved by having sound audit committees capable of performing exceptionally well so as to improve financial reporting quality. The study’s practical contributions are linked to its capacity in highlighting that industrial companies must be cautious when selecting audit committee members